Analisis Kesalahan Siswa dalam Penyelesaian Masalah Aritmatika Sosial Tipe HOTS dengan Prosedur Polya - Irianto, Savitri Oktavia; Nusantara, Toto; Rahardi, Rustanto (Universitas Nahdlatul Ulama Blitar, 2024)
This study is motivated by the importance of social arithmetic in students' social life. This study uses a descriptive qualitative approach that aims to identify students' errors in solving HOTS type social arithmetic problems with the Polya procedure. The subjects of this study were grade VII students of SMP Taman Siswa Malang. Data were obtained from the results of the HOTS type social arithmetic test as many as 2 items in the form of descriptions. The results of this study are errors in the stage of understanding the problem of 30.10% and are included in the fairly high category, errors in the stage of planning problem solving of 28.28% which are included in the fairly high category, errors in the stage of carrying out problem solving plans of 06.26% and are included in the very small category, and errors in the stage of re-checking the solutions obtained of 28.68% and are included in the fairly high category. The causes of errors made by students are quite diverse, one of which is that students forget to write down information known from the questions, students are unable to analyze the existing information, students are not careful when calculating, and students are not used to re-examining what has been done.